Age‐ and sex‐specific prevalence of serious bacterial infections in febrile infants ≤60 days, in Sweden. (27th July 2021) - Orfanos, Ioannis; Alfvén, Tobias; Mossberg, Maria; Tenland, Mattias; Sotoca Fernandez, Jorge; Eklund, Erik A.; Elfving, Kristina
Abstract: Aim: The aim of the study was to describe age‐ and sex‐specific prevalence of serious bacterial infections (SBI: urinary tract infection, bacteraemia, meningitis) among febrile infants ≤60 days in Sweden. Methods: This is a retrospective study in 4 Pediatric Emergency Departments from 2014 to 2017, in previously healthy, full‐term infants ≤60 days with fever without a source. Results: Of the 1, 701 included infants, 214 (12.6%; 95% CI, 11.1–14.3) had an SBI. Urinary tract infection (UTI) was diagnosed in 196 (11.5%; 95% CI, 10.0–13.1) patients. In the ≤28 and 29–60 days age‐groups, meningitis prevalence was 0.9% (95% CI, 0.3–2.0) and 0.3% (95% CI, 0.1–0.8), whereas bacteraemia prevalence was 3.2% (95% CI, 1.9–4.9) and 0.6% (95% CI, 0.2–1.3). The SBI prevalence was higher in boys 16.0% (95% CI, 13.8–18.5) than girls 8.0% (95% CI, 6.2–10.2; p <0.001), due to 2‐fold higher UTI risk. The prevalence of meningitis in boys was 0.3% (95% CI, 0.1– 0.9) vs. 0.7% (95% CI, 0.2–1.6) in girls and of bacteraemia 1.8% (95% CI, 1.0–2.8) vs. 1.0% (95% CI, 0.4–2.0), respectively. Conclusions: The total SBI prevalence was 12.6%, and UTI represented the vast majority. The prevalence of bacteraemia and meningitis was low, particularly in the 29–60 days age group, without significant difference between boys and girls.